Spatial covariation in nutrient enrichment and fishing of herbivores in an oceanic coral reef ecosystem. Issue 3 (11th March 2022) - Holbrook, Sally J.; Wencélius, Jean; Dubel, Alexandra K.; Adam, Thomas C.; Cook, Dana C.; Hunter, Chelsea E.; Lauer, Matthew; Lester, Sarah E.; Miller, Scott D.; Rassweiler, Andrew; Schmitt, Russell J.
Abstract: Both natural and anthropogenic stressors are increasing on coral reefs, resulting in large‐scale loss of coral and potential shifts from coral‐ to macroalgae‐dominated community states. Two factors implicated in shifts to macroalgae are nutrient enrichment and fishing of reef herbivores. Although either of these factors alone could facilitate establishment of macroalgae, reefs may be particularly vulnerable to coral‐to‐algae phase shifts in which strong bottom‐up forcing from nutrient enrichment is accompanied by a weakening of herbivore control of macroalgae via intense fishing. We explored spatial heterogeneity and covariance in these drivers on reefs in the lagoons of Moorea, French Polynesia, where the local fishery heavily targets herbivorous fishes and there are spatially variable inputs of nutrients from agricultural fertilizers and wastewater systems. Spatial patterns of fishing and nutrient enrichment were not correlated at the two landscape scales we examined: among the 11 interconnected lagoons around the island or among major habitats (fringing reef, mid‐lagoon, back reef) within a lagoon. This decoupling at the landscape scale resulted from patterns of covariation between enrichment and fishing that differed qualitatively between cross‐shore and long‐shore directions. At the cross‐shore scale, nutrient enrichment declined but fishing increased from shore to the crest of the barrier reef. By contrast, nutrient enrichment and fishing were positively correlated in the long‐shore direction, with both increasing with proximity to a pass in the barrier reef. Contrary to widespread assumptions in the scientific literature that human coastal population density correlates with impact on marine ecosystems and that fishing effort declines linearly with distance from the shore, these local stressors produced a complex spatial mosaic of reef vulnerabilities. Our findings support spatially explicit management involving the control of anthropogenic nutrients and strategic reductions in fishing pressure on herbivores by highlighting specific areas to target for management actions.